LABORATORY PERFORMANCE ANALYSIS OF AGGREGATES FROM MANOKWARI AS ASPHALTIC CONCRETE BINDER COURSE USING PEN 60/70 BITUMEN WITH POLYMER MODIFIED BITUMEN - Sary De Queljoe, Winda
The use of local aggregates as road construction material is expected to reduce development costs. However, not all regions have sufficient aggregates reserves and quality in accordance with applicable standards. Substandard aggregates is aggregates which is not required at paving specification, such as specific gravity, plasticity, absorption and abrasion that will effect stickiness at asphalt mixture. The main objective of this study is to examine the laboratory performance of aggregates from Manokwari, West Papua in a continuous gradation mixture (ACBC) against the values of stiffness and resistance to deformation. Based on the testing of the physical properties of the aggregates, it was found that the aggregates from Manokwari had high water absorption which affected the amount of bitumen content needed in the mixture. Marshall test results show that the use of Cariphalte modified bitumen in AC-BC mixture that uses substandard aggregates can increase Marshall stability, Marshall Index of Retained Strength, and Indirect Tensile Strength Ratio (ITSR) when compared to AC-BC mixtures using substandard aggregates and Pen 60/70 bitumen. UMATTA test results of modified AC-BC at 35ºC and 45ºC higher than AC-BC mixtures using Pen 60/70 bitumen. The dynamic stability value of modified AC-BC obtained from permanent deformation testing with WTM at temperatures of 45ºC and 60ºC is higher than the dynamic stability value of AC-BC mixtures using Pen 60/70 bitumen. Calculation of number of load application shows that the modified ACBC mixture has a longer life than AC-BC mixture using Pen 60/70 bitumen with lower estimated costs.